The Overlapping angB and angG Genes Are Encoded within the trans-Acting Factor Region of the Virulence Plasmid in Vibrio anguillarum: Essential Role in Siderophore Biosynthesis - Welch, Timothy J. (American Society for Microbiology, 2000)
Products encoded in the trans-acting factor (TAF) region are necessary for the biosynthesis of anguibactin and for maximal expression of iron transport and biosynthesis genes in the plasmid-encoded iron-scavenging system of Vibrio anguillarum. Here we identify angB, a locus located in the TAF region, which encodes products essential for anguibactin biosynthesis. We demonstrate that a 287-amino-acid polypeptide, encoded by angB and designated AngB, has an isochorismate lyase activity necessary for the synthesis of 2,3-dihydroxybenzoic acid, an anguibactin biosynthesis intermediate. Complementation of various angB mutations provided evidence that an additional, overlapping gene exists at this locus. This second gene, designated angG, also has an essential biosynthetic function. The angG gene directs the expression of three polypeptides when overexpressed in Escherichia coli, all of which are translated in the same frame as AngB. The results of site-directed mutagenesis and in vivo phosphorylation experiments suggest that the carboxy-terminal end of AngB and the AngG polypeptide(s) function as aryl carrier proteins involved in the assembly of the anguibactin molecule. Our results also show that the regulatory functions of the TAF are encoded in a region, TAFr, which is distinct from and independent of the angB and angG genes.